Vertiminaponik sebagai Modal Ekonomi Masyarakat Kampung Sewu dalam Praktik Mitigasi Bencana Banjir - Dewi, Annisa Nindya (Asketik: Jurnal Agama dan Perubahan Sosial, 2019)
by the people of Kampung Sewu who live in the area which is prone to floods in the Bengawan Solo River in carrying out practices of flood disaster mitigation. Vertiminaponics is a program created by PMI Surakarta City with SIBAT Sewu by planting vegetables in hard pipes which have been perforated and given fertilized soil inside, then under the hard pipes, the fish are kept in jerry cans which are combined. The dirt produced by the fish will be a fertilizer for vegetable plants that grow on it. Financial capital has a vital role in practicing flood disaster mitigation. Sociologically, financial capital is an addition to the knowledge that causes economic achievements to increase. Therefore vertiminaponics became a strong financial capital for the people of Kampung Sewu in practicing flood disaster mitigation due to the overflow of the Bengawan Solo River. This qualitative research uses a phenomenological approach. The source of primary data is obtained from the results of in-depth interviews and secondary data sources are obtained from scientific books, journals, and documents owned by informants. Direct observation, in-depth interviews, and documentation are used as data collection techniques. This study used purposive sampling in selecting informants while the validity of the data using source triangulation. The results of this study indicate that vertiminaponics was carried out by PMI Surakarta City with SIBAT Sewu to be practiced together with the community of Sewu Village. Vertiminaponics as one of the flood disaster mitigation practices of the people of Kampung Sewu due to the overflow of the Bengawan Solo River was able to become a fairly strong financial capital. Vertiminaponic maintenance is not difficult, besides that the vegetable plants produced are also classified as organic vegetables and do not require extensive land. Sewu village has a community that is resilient to floods. The thing that happened during flood disaster was that the people of Sewu Village experienced obstacles in meeting food needs. Thus vertiminaponics is a financial capital for the people of Kampung Sewu in fulfilling food needs, especially in the event of a flood.